Making the difficult career transition: Writing the next chapter during the great resignation or in the future - Coppola, Paul J.; Young, Aprille F. (Frontiers in Psychology, 2022)
During the midst of the Great Resignation, over 4.5 million people have changed jobs (Davidson, 2022). While a job change does not register as one of the top three drivers of stress, career transition related stress does present itself as one of the top twenty-five causes (Davidson, 2022). This stress can be reduced through social support models (Greer & Kirk, 2022), career transition planning, and personal brand strategy frameworks (Rensburg & Ukpere, 2014). These adaptive change models become part of a continuous learning and growth-process. This literature review aims to contribute to the industry and define career transition through a more holistic personal brand strategy utilizing a wide range of disciplines considering the challenges and opportunities presented during the Great Resignation. Keywords: adaptive leadership and change, branding, career change, career transition, development, Great Resignation, personal branding